2017
DOI: 10.3136/fstr.23.733
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Short-Term Intake of Wheat Bran with Different Particle Sizes on the Murine Intestinal Environment

Abstract: Wheat bran has a high dietary fiber content. In this study, we investigated the effects of short-term intake of wheat bran on intestinal environment in a murine model. Mice were fed with AIN-93G for 1 week, followed by experimental diets containing wheat bran with an average particle size of 53 μm (powdered) or 350 μm (granulated) for 1 additional week. During a 4-week period (twice-repeated feeding cycles), the ratio of bacteria belonging to the families Prevotellaceae and S24-7 increased in murine feces afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…A previous study demonstrating the beneficial effects of wheat bran on IgA production used a high dose (~2500 mg/kg for 4 weeks, equivalent to ~750 mg AX/kg) [ 19 ]. Another study demonstrated that elevated SCFA levels and IgA production substituted equal amounts of wheat-bran-derived fiber with 5% cellulose in the AIN-93G diet [ 17 ], which may be calculated as approximately 1200 mg/kg daily intake of AX per mouse. A high dose of AX elevated the propionate and butyrate levels, even 1 week after AX feeding, which was maintained until the end of the experiment (at 4 weeks).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study demonstrating the beneficial effects of wheat bran on IgA production used a high dose (~2500 mg/kg for 4 weeks, equivalent to ~750 mg AX/kg) [ 19 ]. Another study demonstrated that elevated SCFA levels and IgA production substituted equal amounts of wheat-bran-derived fiber with 5% cellulose in the AIN-93G diet [ 17 ], which may be calculated as approximately 1200 mg/kg daily intake of AX per mouse. A high dose of AX elevated the propionate and butyrate levels, even 1 week after AX feeding, which was maintained until the end of the experiment (at 4 weeks).…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of wheat bran and AX on the gut microenvironment and health have been extensively studied. Balb/c mice fed wheat bran showed increased luminal IgA production, which coincided with Clostridiales overrepresentation and elevated SCFA levels [ 17 , 18 ]. This IgA induction may be attributed to the AX from the wheat bran because soluble AX feeding also augmented IgA production in the Balb/c mice [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…DFs can also be associated with side effects such as gastrointestinal symptoms, partly due to gas production or bloating caused by rapid fermentation ( Rodriguez et al, 2020 ). The fermentability of DFs, which could be improved by decreasing the particle size of materials, was shown by the increasing amount of produced butyric acid in the colon ( Iwai et al, 2017 , Tuncil et al, 2018 ). The hydration and antioxidant properties of DFs were enhanced by decreasing the particle size of rice bran ( Zhao et al, 2018 ).…”
Section: The Physicochemical Properties Of Dfs From Rice Bran and Whe...mentioning
confidence: 99%
“…Sample preparation of wheat bran (particle sizes D 50 = 53 µm [powdered] and D 50 = 350 µm [granulated]) was performed according to our reported method. 22 The dietary fiber contained in AIN-93G was replaced by powdered wheat bran (PWB group) and granulated wheat bran (WB group) containing the same amount of fibers. The composition of diets is shown in Table 1.…”
Section: Wheat Bran Samplementioning
confidence: 99%
“…In a previous study, we investigated the effects of short-term intake (twice-repeated feeding cycles during a 4 weeks period) of wheat bran on the intestinal environment in a murine model. 22 However, the benefits of long-term intake of wheat bran and the in vivo effects of particle-size differences remain unclear. In this study, we investigated the effects of wheat bran with 2 different particle sizes on intestinal microbiota composition, SCFA production, and IgA secretion in long-term intake (4 weeks continuous feeding) in mice.…”
mentioning
confidence: 99%